Effectiveness of disinfectants used in hemodialysis against both Candida orthopsilosis and C. parapsilosis sensu stricto biofilms - Pires, Regina Helena [UNESP]; De Fátima Da Silva, Julhiany [UNESP]; Martins, Carlos Henrique Gomes; Almeida, Ana Marisa Fusco [UNESP]; Soares, Christiane Pienna [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (American Society for Microbiology, 2013)
Biofilms have been observed in the fluid pathways of hemodialysis machines. The impacts of four biocides used for the disinfection of hemodialysis systems were tested against Candida parapsilosis sensu stricto and Candida orthopsilosis biofilms generated by isolates obtained from a hydraulic circuit that were collected in a hemodialysis unit. Acetic acid was shown to be the most effective agent against Candida biofilms. Strategies for effective disinfection procedures used for hemodialysis systems should also seek to kill and inhibit biofilms. Copyright © 2013, American Society for Microbiology. All Rights Reserved.
Keywords: acetic acid; biocide; bacterium isolate; biofilm; Candida orthopsilosis; Candida parapsilosis; controlled study; disinfection; hemodialysis; nonhuman; priority journal